Regional Head to Overcome Corruption Strategy in Indonesia - Mulyana, Yaya; Achdiat,; Amirulloh, Rangga Muslim (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to examine the phenomenon of corruption that occurs in the regions, especially the Regional Head Operations (OTT) of corruption by the KPK which is quite alarming after decentralization as stipulated in Law No. 23/2014 Regional Government and Law No. 33 of 2004 concerning Regional Central Fiscal Balance. The elections that are intended to produce the best leaders in their regions by direct and open elections actually give birth to troubled leaders who betray the people's mandate. The method used in the activity is a descriptive method through a qualitative approach. With this method and approach, it is expected to be able to describe various problems in their entirety and comprehensively, so that the results of the problem analysis can be used as a basis for understanding phenomena and giving birth to a concept of preventing and controlling corruption of regional heads. Considering that many cases of regional head corruption occur, the perspective must not be seen as mere incidental and human error, but it is a fundamental and comprehensive system error, so it must be improved systematically starting from the recruitment, process and procedure of the local elections to the authority of the elected regional head.